Overview of multimorbidity research in India: A scoping review - Parul Puri; Siaa Girotra; Arpita Ghosh (Journal of Multimorbidity and Comorbidity)
Objectives Demographic and epidemiological shifts have led to people living with coexisting health issues, known as ‘multimorbidity’. Given India’s aging population, rising noncommunicable disease burden, chronic infections, fragmented healthcare, and reliance on specialist care, a scoping review is needed to understand the extent and nature of research on multimorbidity in India. Methods A comprehensive search was conducted across PubMed, Cochrane, and Embase for studies focused on multimorbidity, with information specifically from India. Two reviewers independently screened the results and extracted information on definitions, including use of cut-offs or a minimum number of conditions, data and methods, patterns, risk factors and outcomes. Results were synthesized using descriptive statistics and narrative synthesis. Results Of 9954 identified studies, 100 were included in the final synthesis. Of these, 62 were secondary analyses, 35 collected primary data, and 3 used administrative data. Most studies defined multimorbidity as two or more chronic or long-term conditions but did not specify whether long-term infections or mental health conditions were included. The number of conditions varied between 4 and 22. Circulatory, endocrine-nutritional-metabolic, and respiratory diseases were most frequently included. Beyond simple disease counts, combinations were reported in 15 studies. Healthcare utilization, out-of-pocket expenditure, and quality of life were commonly studied, mostly using cross-sectional designs. Conclusion A standardised panel of conditions with clear definitions is needed for measuring multimorbidity. Conditions should be ascertained through a combination of self-report, physical examinations, and laboratory investigations. Additionally, longitudinal studies focused on multimorbidity, and its outcomes are needed to strengthen evidence base in India.